Nilai-Nilai Syariah Islam dalam Album Masih Ada Waktu Ebiet G Ade dan Implikasi dalam Pembelajaran Teks Puisi - Utami, Nanda Reski; Nursaid; Hendri, Bunga Febrimora (Journal of Practice Learning and Educational Development, 2023)
This research aims at this research there are two things. First, to describe Islamic sharia values ​​in the album, there was still time for Ebiet G.Ade. Second, to describe the implications of the album, there is still time for Ebiet G Ade to study poetry texts. This type of research is qualitative research. The method used is descriptive method. The data sources of this research are Islamic sharia values ​​related to Islamic sharia values ​​in the album still exists when Ebiet G. Ade. The research instrument used in this study was the researcher himself. Data collection technique in this research is observation technique. There are three data analysis techniques, (1) data reduction, (2) data presentation, and (3) data verification. There are two data validation techniques in this study, (1) extension of the observation period and (2) increasing accuracy in observations. The findings of the data in this study. First, the sharia value of moral science. Second, the sharia value of monotheism. Third, the sharia value of fiqh.